Neutrophil extracellular traps: New players in cancer research - Zhao, Junjie; Jin, Jiaqi (Frontiers in Immunology, 2022)
Tumor-associated neutrophils (TANs) constitute a substantial proportion of tumor-associated immune cells infiltrating the tumor microenvironment. Recently, most TANs in primary tumors or metastatic sites have been described as neutrophil extracellular traps (NETs). A NET is a structure consisting of neutrophil proteins and DNA that are expressed upon cell activation. In addition to the classical role that NETs play in innate immunity against infection and injuries, similar to neutrophils, NETs have been implicated extensively in cancer progression, metastatic dissemination, and therapy resistance. The purpose of this review is to describe recent investigations into NETs and the roles they play in tumor biology and to explore their potential as therapeutic targets in cancer treatment.